ChemInform Abstract: Asymmetric Synthesis of Tetrahydroquinolines Through Supramolecular Organocatalysis. Issue 48 (2nd December 2014) - Ramachary, Dhevalapally B.; Shruthi, Kodambahalli S.
Abstract Medicinally important title compounds (IV) are prepared via enantioselective Michael addition of acetone to azido‐nitrovinyl‐benzenes (I), followed by reductive amination.